How Naïve Is the Market’s Use of Firm‐Specific Earnings Information? - Mendenhall, Richard R. (Journal of Accounting Research, 2002)
Recent studies suggest the apparent delay in the stock‐price response to earnings announcements (i.e., post‐earnings announcement drift) is caused by investors who underestimate the autocorrelation of seasonally‐differenced earnings (persistence). I present results that suggest: (1) a firm’s future persistence is predictable on the basis of its past persistence; (2) the immediate stock‐price response to earnings is positively related to historical persistence; (3) post‐earnings‐announcement drift is independent of historical persistence; and (4) consistent with (2) and (3), the difference between a firm’s current observed persistence and that implied in stock prices is independent of its historical persistence. These results extend prior research by demonstrating that investors are aware not only that seasonally‐differenced earnings are autocorrelated, but that investors recognize firm‐specific differences in the magnitude of the autocorrelation.